2019
DOI: 10.1002/jlb.3hi0918-348rr
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: TLR3 activation inhibits food allergy in mice by inducing IFN-γ+ Foxp3+ regulatory T cells

Abstract: The pathologic feature of food allergy (FA) is the aberrant Th2-biased immune response in the intestine. Regulatory T cells (Tregs) play an important role in the suppression of aberrant immune response. The activities of the TLRs regulate multiple cell functions. This study aims to investigate the role of TLR3 activation in the regulation of Th2-biased immune response in the intestine by the generation of inducible Tregs (iTregs). In this study, polyinosinic polycytidylic acid (polyI:C) was used as an activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Taken together, our findings suggest that GMP protects on GI manifestations and intestinal alterations associated with FA, by shifting the immune balance towards the type 1 and regulatory profiles, and away from the type 2 response; and this effect might be mediated, at least partially, by stimulating the production of TGF-β at the intestinal level. Our results are supported by findings showing that in CD4+ T cells from FA mice GATA3 forms a complex with Foxp30 that prevents Foxp3 movement to TGF-β promoter locus [ 103 ]. When T-bet expression is increased, it binds GATA3 and dissociates Foxp3, which has the opportunity to move to TGF-β promoter.…”
Section: Discussionsupporting
confidence: 86%
“…Taken together, our findings suggest that GMP protects on GI manifestations and intestinal alterations associated with FA, by shifting the immune balance towards the type 1 and regulatory profiles, and away from the type 2 response; and this effect might be mediated, at least partially, by stimulating the production of TGF-β at the intestinal level. Our results are supported by findings showing that in CD4+ T cells from FA mice GATA3 forms a complex with Foxp30 that prevents Foxp3 movement to TGF-β promoter locus [ 103 ]. When T-bet expression is increased, it binds GATA3 and dissociates Foxp3, which has the opportunity to move to TGF-β promoter.…”
Section: Discussionsupporting
confidence: 86%
“…As a typical cytokine secreted by Th2 cells, IL-4 stimulates B lymphocytes differentiation and IgE production, thereby inducing mast cell degranulation and aggravating allergic reactions (Anna et al, 2023). As cytokine secreted by Th1 cells, IFN-γ can reduce the inflammatory response caused by FA, and its increase will inhibit the secretion of Th2 cytokines (Hong et al, 2019). In the present study, ies, Lachnospiraceae_NK4A136_group is a potential probiotic involved in the Hsp70-NF-κB signaling to ameliorate colonic damage and inflammation caused by FA (Liu et al, 2023).…”
Section: F I G U R Ementioning
confidence: 73%
“…As a typical cytokine secreted by Th2 cells, IL‐4 stimulates B lymphocytes differentiation and IgE production, thereby inducing mast cell degranulation and aggravating allergic reactions (Anna et al., 2023). As cytokine secreted by Th1 cells, IFN‐γ can reduce the inflammatory response caused by FA, and its increase will inhibit the secretion of Th2 cytokines (Hong et al., 2019). In the present study, it was found that the serum levels of Th1 type cytokine IFN‐γ were increased, whereas the Th2 type cytokine IL4 was decreased after the intervention of Se‐TPS.…”
Section: Discussionmentioning
confidence: 99%
“…24 Treg generation has been employed in the studies of FA treatment. 24,25 In addition, generating Tregs is one of the major goals in Ag-specific immunotherapy. 26 The present study added IL-2 into the mExosomes.…”
Section: Discussionmentioning
confidence: 99%